2013
DOI: 10.1007/s00125-013-2860-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of metabolic control and QTc prolongation on all-cause mortality in patients with type 2 diabetes and foot ulcers

Abstract: Aims/hypothesis The increased all-cause mortality in patients with chronic diabetic foot ulcers cannot fully be explained by traditional cardiovascular risk factors. The significance of heart-rate-corrected QT (QTc) prolongation, a finding often seen in these patients, is unknown. Recently, the importance of metabolic control and hypoglycaemia has been discussed. The aim of this study was to evaluate the impact of different HbA 1c levels and QTc prolongation on all-cause mortality in the high-risk population o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 47 publications
4
25
1
Order By: Relevance
“…Previous studies in patients with type 2 diabetes have reported that the relationship between HbA1c, all‐cause mortality and other outcomes was not a direct association but better characterized by a J‐shaped, V‐shaped or U‐shaped association . In this study, we not only found that the pattern of association between differing levels of HbA1c and all‐cause mortality differed within specific glucose‐lowering regimens, but also that this pattern of association differed between differing glucose‐lowering regimens.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studies in patients with type 2 diabetes have reported that the relationship between HbA1c, all‐cause mortality and other outcomes was not a direct association but better characterized by a J‐shaped, V‐shaped or U‐shaped association . In this study, we not only found that the pattern of association between differing levels of HbA1c and all‐cause mortality differed within specific glucose‐lowering regimens, but also that this pattern of association differed between differing glucose‐lowering regimens.…”
Section: Discussionsupporting
confidence: 56%
“…7 Thus, the optimum target for glucose control in patients with diabetes remains uncertain. This uncertainty is further complicated because both randomized trials 8,9 and observational studies 7,[10][11][12][13][14][15][16][17][18][19][20]25,26 have been unable to demonstrate a consistent pattern of association between levels of glucose control and adverse outcome, nor to explain why this may be the case.…”
mentioning
confidence: 99%
“…However, this excess risk cannot fully be explained by a higher prevalence of cardiovascular disease (CVD) or known CVD risk factors [22]. Lately, several studies have indicated the importance of long QTc time, a well-known predictor for malignant arrhythmias and death, as a predictor of all-cause mortality in patients with diabetes [4,5]. QTc prolongation is more frequently found in patients with diabetes than in non-diabetic patients [7].…”
Section: Discussionmentioning
confidence: 99%
“…This excess mortality has in part, been explained by an increased burden of traditional cardiovascular risk factors, such as hypertension, myocardial infarction, heart failure, renal dysfunction and smoking. However, these risk factors cannot fully explain this excess mortality risk, and lately studies have demonstrated an association between heart rate corrected QT interval (QTc) and all-cause and cardiovascular mortality in the general population [2,3] as well as in people with diabetes [4][5][6]. Several factors, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…QT prolongation has been found in various experimental diabetes animal models, which mimic type 1 and type 2 diabetes in human beings [8,9]. While investigating the QTc interval prolongation in both type 1 and type 2 diabetes, various studies have postulated such prolongation to be associated with long-term mortality from all-causes, cardiovascular, cardiac, and ischemic heart disease [10,11]. The prevalence of QTc interval prolongation reported in diabetes are variable [12,13]; the prevalence of QTc prolongation in type 2 diabetes is 30.1% among Chinese population obtained from a outpatient retrospective study [14] and 34.6% in a hospital-based cross sectional population study from European patients [15].…”
Section: Introductionmentioning
confidence: 99%